2014
DOI: 10.1002/cvde.201407113
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Properties of Multilayered Eu2O3 and TiO2 Grown by Atomic Layer Deposition**

Abstract: Atomic layer deposition (ALD) is used to control the interatomic interactions of Eu and Ti in multilayered structures, as measured by characterizing the luminescent properties of the deposited material. Luminescent multilayer structures of Eu 2 O 3 and TiO 2 are deposited as thin films by ALD at 300°C using Eu(thd) 3 /O 3 and TiCl 4 /H 2 O (thd ¼ 2,2,6,6-tetramethyl-3,5-heptanedione) as precursor systems. The individual layer thickness of the multilayered structure is produced from first N ALD cycles Eu 2 O 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Here, it should be mentioned that the ALD technique (by that time, atomic layer epitaxy or ALE) was originally invented to meet the challenge of depositing high‐quality thin films for electroluminescence displays . Although basic thermal ALD processes have been available for most of the lanthanoid (Ln) oxides for a while , there are only a few reports on luminescent thin films fabricated by ALD or the related MLD (molecular layer deposition) technique .…”
Section: Introductionmentioning
confidence: 99%
“…Here, it should be mentioned that the ALD technique (by that time, atomic layer epitaxy or ALE) was originally invented to meet the challenge of depositing high‐quality thin films for electroluminescence displays . Although basic thermal ALD processes have been available for most of the lanthanoid (Ln) oxides for a while , there are only a few reports on luminescent thin films fabricated by ALD or the related MLD (molecular layer deposition) technique .…”
Section: Introductionmentioning
confidence: 99%
“…[65,66] With the aid of post-deposition annealing to produce Fe3O4, alternating layers of Al2O3 and Fe3O4 have shown tunable microwave absorption properties. [67] The photoluminescence of Eu2O3/TiO2 stacks have been investigated with control of layer thickness down to one unit cell, [68] while Al2O3/Y2O3 multilayers have been studied for optical waveguide purposes. [69] With the flexibility ALD provides, changing between depositions of different materials is, as mentioned, easy.…”
mentioning
confidence: 99%
“…[45][46][47][48][49][50][51][52][53][54][55][56][57]61 Also, it has been shown that amorphous Eu 2 O 3 exhibits similar luminescence ( 5 D 0  7 F J transitions, relative intensities, and line-broadening) upon irradiation at 325 nm. 63,64 Nanocrystalline Eu 2 O 3 nanotubes give rise to a similar emission fingerprint when excited at 254 nm. 65 Therefore Eu-based luminescence could arise from TiO 2 excitation and energy transfer to Eu 3+ or from direct excitation of the O  Eu LMCT band.…”
Section: Characterization Of Eu 3+ -Tio 2 Nanocrystalsmentioning
confidence: 95%